REKONSTRUKSI VARIASI BULANAN SALINITAS DI JALUR ARUS LINTAS INDONESIA SELAMA ~ 200 TAHUN: REKAMAN SALINITAS DARI δ18О KARANG BUNAKEN DAN BALI - Hernawan, Indra; Cahyarini, Sri Yudawati; Putri, Mutiara (Jurnal Geologi dan Sumberdaya Mineral, 2012)
Salinity is one of important parameter in oceanographic studies. The long timeseries oceanographic data is required to more understand the variability of oceanographic condition. Coral geochemical proxies overcome the shortcoming of instrumental data availibility. δ18О contents in coral skeleton is influenced by sea surface temperature and δ18О seawater. δ18О seawater is influenced by salinity. In this study salinity is reconstructed using coral δ18О and SST from the data model. δ18О from Bunaken and Padang Bai (Bali) corals are used in this study. SST data from the ERSST, SODA and HAMSON are used to reconstruct salinity. This study result in that the Bunaken coral records the local salinity variation in monthly and annual mean resolution. Padang Bai coral records better salinity in annual mean variation than in monthly variation. In both region, salinity variation in decadal resolution does not show significantly different.Keywords: Salinity, Sea surface temperature, δ18О, coral, Bunaken and Bali.